Plant Communities in Some Sal (Shorea robusta) Forests of U.P. - Bhatnagar, H. P. (Indian Forester, 1960)
Floristic composition of some representative samples of some Utter Pradesh Sal forests has been worked out to differentiate the constituent plant communties and their successional trends. In all seven plants communities were recognized. Successional relationship among different communities indicate that in dry sal types Sal Anogeissus-Colebruokia and Sal-Ougeinia-Carrissa-Sida communities are lower stages which tend to progress towards Sal-Terminalia-Glycosmis community under improved biotic conditions. Similarly in moist Sal types the Sal-Ougzinia-Clebrookia community tends towards Sal-Terrninalia-Moghania community. The latter community and Sal-Lagerstroemia-Pogostermon community are more or less stable aggregations under normal conditions but occur in different climatic and forest zones and in respect of stability and maturity they occupy a corresponding position. Sal-Termninalia-Moghania community tend to change into Sal-Syzygiurn-Randia-Ageratum community under damper conditions and may thus be a post climax stage occurring in specially favourable situations.